The New York City Consolidation Act, as in Force in 1891, at 209, Gunpowder and other explosives. Sale thereof regulated, § 455 (Vol. 1, 1891) - (:unkn) unknown (General Publisher, 1890)
No person shall manufacture, have, keep, sell, or give away any gunpowder, blasting powder, gun-cotton, niro-glycerine, dualin, or any explosive oils or compounds, within the corporate limits of the city of New York, except in the quantities limited, in the manner, and upon the conditions herein provided, and under such regulations as the board of fire commissioners shall prescribe
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER